MAHAR DALAM PERNIKAHAN SEBAGAI HAK EKONOMI PEREMPUAN: KAJIAN TRADISI KEAGAMAAN - Asma, Khusnul; Yunita, Ita; Machrus, Ali (Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2024)
Dowry in marriage is one of a woman's absolute rights or the wife's rights as a result of marriage. The dowry is given by the prospective husband as part of an expression of the seriousness of a man's desire for a woman, as well as a sign of a prospective husband's affection for his prospective wife. The dowry is also used as a symbol of appreciation to glorify, honor, and is a symbol of the desire to make the woman who will become his wife happy. Providing a dowry is a form of protecting women's rights to take care of and manage their rights. This means that Islam highly upholds women's rights while providing legal protection to women. In this case, the author makes an important note about how a wife should know and receive her dowry after the marriage contract takes place. By knowing and receiving her dowry, a woman, in this case a wife, knows her rights clearly and can then manage and utilize those rights as one of her economic rights without obstacles and difficulties. Dowry is an absolute right that women must have, not just a formality during the marriage contract. Therefore, it is necessary to clarify the dowry, both regarding the form, type and exact amount so that women's economic rights can be fulfilled both in marriage and after divorce.